2016
DOI: 10.1016/j.cpr.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

‘Jumping to conclusions’ data-gathering bias in psychosis and other psychiatric disorders — Two meta-analyses of comparisons between patients and healthy individuals

Abstract: There has been an increase in attention to studying shared mechanisms underlying psychiatric disorders. The 'Jumping to conclusions' (JTC(1)) bias, a tendency to make decisions with certainty based on insufficient information, has been reported in patients with psychosis, and process-based treatment protocols targeting this bias have recently been developed. This review aimed to investigate to what extent the JTC bias, measured by various tasks, is associated with psychotic disorders and other psychiatric diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
86
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 80 publications
5
86
1
Order By: Relevance
“…Participants diagnosed with clinical delusions requested significantly fewer beads than psychiatric and healthy controls. Dozens of beads task studies have subsequently been published, many of which have replicated this result (Dudley, Taylor, Wickham, & Hutton, 2016;Garety & Freeman, 1999, 2013McLean, Mattiske, & Balzan, 2016;So, Siu, Wong, Chan, & Garety, 2016). Furthermore, limited data gathering in the beads task is associated with higher delusional ideation in nonclinical populations (Ross, McKay, Coltheart, & Langdon, 2015), which is consistent with theories that propose that clinical delusions lie on a continuum with normal belief (Heriot-Maitland & Peters, 2015;Larøi, Raballo, & Bell, 2015;Linscott & van Os, 2013).…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Participants diagnosed with clinical delusions requested significantly fewer beads than psychiatric and healthy controls. Dozens of beads task studies have subsequently been published, many of which have replicated this result (Dudley, Taylor, Wickham, & Hutton, 2016;Garety & Freeman, 1999, 2013McLean, Mattiske, & Balzan, 2016;So, Siu, Wong, Chan, & Garety, 2016). Furthermore, limited data gathering in the beads task is associated with higher delusional ideation in nonclinical populations (Ross, McKay, Coltheart, & Langdon, 2015), which is consistent with theories that propose that clinical delusions lie on a continuum with normal belief (Heriot-Maitland & Peters, 2015;Larøi, Raballo, & Bell, 2015;Linscott & van Os, 2013).…”
Section: Introductionsupporting
confidence: 80%
“…1 Such proposals are consistent with recent meta-analyses that have found that reduced data gathering is associated with increased self-reported delusional ideation (Ross et al, 2015) and psychotic diagnoses (Dudley et al, 2016;McLean et al, 2016;So et al, 2016). In addition, recent studies have reported that data gathering in the beads task is associated with performance in an analytic reasoning task (Brosnan, Hollinworth, Antoniadou, & Lewton, 2014) and self-reported "systemising" (Brosnan, Ashwin, & Gamble, 2013).…”
Section: Introductionsupporting
confidence: 65%
“…In line with the idea that overhasty and erroneous perceptual inferences from irrelevant noise information are implicated in hallucinations and hallucination-proneness, hallucinatory experiences have been repeatedly associated with a greater tendency to perceive illusory contents in auditory noise [9,10]. Moreover, delusional ideation has been consistently linked to “jumping to conclusions” (JTC, see [1113] for detailed meta-analyses), a cognitive reasoning bias that leads to a rash acceptance of hypotheses based on little evidence. However, it is a matter of ongoing debate, which particular cognitive alteration predisposes delusional and delusion-prone individuals for an overhasty acceptance of possible hypotheses [1417].…”
Section: Introductionmentioning
confidence: 98%
“…Garety et al have consistently argued that abnormal beliefs derive from a "jumping to conclusions bias." 17,18 Although reasonable people can disagree, this bias may be analogous to failing to inhibit or suppress the discomfort of not knowing. It may alternatively relate to failures in response selection (selecting a nondominant response), performance monitoring, or it may relate to something else altogether (these researchers themselves also describe it variously as a data-gathering or reasoning bias).…”
mentioning
confidence: 99%
“…Much of this work is narrowly balanced on a single task (the beads task), performance on which correlates strongly with working memory (another RDoC construct) and IQ. 19 Differences between psychotic patients and controls on the task are sizeable, Cohen's d = 0.61, 18 but modest compared to d ≈ 1.00 for many other neuropsychological main effects. Risen's context for thinking about how failures in any of several cold cognitive processes might allow for the formation and maintenance of abnormal beliefs may profitably be applied to expanding our thinking about the cognitive neuroscience constructs relevant to delusions.…”
mentioning
confidence: 99%